2011
DOI: 10.1038/ijo.2011.116
|View full text |Cite
|
Sign up to set email alerts
|

Association between impulsivity, reward responsiveness and body mass index in children

Abstract: Background: Childhood obesity is a major health problem. An association between children's body mass index (BMI) and overeating has been established, but mechanisms leading to overeating are poorly understood. The personality characteristics impulsivity and reward responsiveness may be involved in the tendency to overeat. Impulsivity might relate to overeating through poor inhibition of food intake; reward responsiveness through the rewarding value of food. Objective: This study aimed to reveal the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 39 publications
1
60
2
1
Order By: Relevance
“…A recent study examining inhibitory control in children suggested that high impulsivity was linked with obesity (31). Impulsivity and reward sensitivity have specifically been found to influence BMI through overeating (32) and high levels of impulsivity may be associated with a rebound effect after eating (7). Impulsivity has also been linked to weight loss failure, with more impulsive children losing less weight.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study examining inhibitory control in children suggested that high impulsivity was linked with obesity (31). Impulsivity and reward sensitivity have specifically been found to influence BMI through overeating (32) and high levels of impulsivity may be associated with a rebound effect after eating (7). Impulsivity has also been linked to weight loss failure, with more impulsive children losing less weight.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired response inhibition is a behavioral trait of which impaired satiety may be one manifestation. A related trait – impulsivity – has been linked to obesity [36-38] and poor obesity treatment outcomes in children [37]. …”
Section: Discussionmentioning
confidence: 99%
“…(Anzman and Birch 2009;Van den Berg et al 2011). Impulsive children exhibit externally motivated, emotional eating, but, notably, not when parents monitor them (Farrow 2012).…”
Section: ___________________mentioning
confidence: 99%